Examining a research boundary within natural disaster management: qualitative case study. (9th May 2019) - Ha, Kyoo-Man
In recognition of scientific research's key role in the field of natural disaster management, this paper aims to remove a research boundary in the Korean setting, with the support of impact assessment theories. The hypothesis is that "if a boundary exists between domestic research and international research in the Korean field of natural disaster management, then it deserves appropriate alternatives." A qualitative case study was used to compare domestic research and international research via government research, business research, college research and non-governmental organisation (NGO) research. Upon acceptance of the hypothesis, a key finding obtained points to Korea's need to develop research boundary awareness. Accordingly, the international community has to setup multilanguage networks, include a research boundary into the framework, accommodate multiple cultures in the research, and consequentially make better decisions when managing natural disasters.